Tradisi Albarzanji: Menguak Peran Penting Ritual Keagamaan dalam Pembentukan Maharah Istima’ pada Anak-anak Desa Teluk Papal, Kecamatan Bantan - Alwi, Muhammad; Arwani, M. Khairul; Susanti, Triana; Efendi, Muhammad; Afifah, Sarah (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2023)
This article discusses the important role of the Albarzanji tradition in developing istima' (listening skills) in the children of Teluk Papal Village, Bantan Subdistrict, which emphasizes the values of local wisdom on the island of Bengkalis. In this research, three data collection techniques were used: observation, questionnaires, and documentation. The data analysis used in this study includes Miles and Huberman's Model, which involves data reduction, data processing, and data evaluation/review. The research findings indicate that the Albarzanji activities carried out in Dusun I, Teluk Papal Village, have the potential to enhance istima' skills, as evidenced by the proficiency of the Teluk Papal Village community in listening to the Albarzanji book, understanding its meaning, and using everyday Arabic vocabulary mentioned in the Albarzanji book.